2007
DOI: 10.1074/jbc.m703276200
|View full text |Cite
|
Sign up to set email alerts
|

The Insulin-like Growth Factor Type 1 and Insulin-like Growth Factor Type 2/Mannose-6-phosphate Receptors Independently Regulate ERK1/2 Activity in HEK293 Cells

Abstract: Insulin-like growth factor types 1 and 2 (IGF-1; IGF-2) and insulin-like peptides are all members of the insulin superfamily of peptide hormones but bind to several distinct classes of membrane receptor. Like the insulin receptor, the IGF-1 receptor is a heterotetrameric receptor tyrosine kinase, whereas the IGF-2/ mannose 6-phosphate receptor is a single transmembrane domain protein that is thought to function primarily as clearance receptors. We recently reported that IGF-1 and IGF-2 stimulate the ERK1/2 cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
36
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 52 publications
6
36
0
1
Order By: Relevance
“…PLF1 is a ligand for the Gi proteincoupled IGF2R (25,36), which mediates prolactin-induced alveolar development in the mammary gland through activation of ERK and Jak2 (6,27). Receptor activation by PLF1 activates ERK (20,25) and transcription factor AP-1 (63) and is blocked by pertussis toxin (20,25), which catalyzes ADPribosylation of the Gi␣ subunit to prevent its interaction with cell membrane receptors (8). This mechanism is consistent with the inhibitory effect of pertussis toxin on PLF1-mediated ERK activation by COMMA/Msi-conditioned medium, as well as inhibition of ERK activation by PLF1 depletion from COMMA/Msi1-conditioned medium.…”
Section: Discussionmentioning
confidence: 99%
“…PLF1 is a ligand for the Gi proteincoupled IGF2R (25,36), which mediates prolactin-induced alveolar development in the mammary gland through activation of ERK and Jak2 (6,27). Receptor activation by PLF1 activates ERK (20,25) and transcription factor AP-1 (63) and is blocked by pertussis toxin (20,25), which catalyzes ADPribosylation of the Gi␣ subunit to prevent its interaction with cell membrane receptors (8). This mechanism is consistent with the inhibitory effect of pertussis toxin on PLF1-mediated ERK activation by COMMA/Msi-conditioned medium, as well as inhibition of ERK activation by PLF1 depletion from COMMA/Msi1-conditioned medium.…”
Section: Discussionmentioning
confidence: 99%
“…Two distinct binding sites accommodate IGF-II and mannose-6-phosphate (Braulke, 1999). Type I and II receptors may mediate Erk 1/2 phosphorylation provoked by IGF-I and IGF-II, respectively (El-Shewy et al, 2007). By knocking down type I IGF-IR, the activation of Erk p42/44 elicited by IGF-I is substantially abrogated, whereas that of IGF-II persists.…”
Section: B Insulin-like Growth Factor-i Receptorsmentioning
confidence: 99%
“…In contrast, interfering with the type II receptor had little effect on IGF-I signaling to Erk, whereas the activities of IGF-II on the activation of this kinase were reduced. Thus, type I and II receptors might function independently with regard to Erk activation, and IGF-II might exert at least some of its actions through the type II receptor (El-Shewy et al, 2007). The signaling initiated through IGF-IR begins with a conformational change provoked by receptor ligation and involves a number of well used pathways in tissues in which IGF-I exerts its actions.…”
Section: B Insulin-like Growth Factor-i Receptorsmentioning
confidence: 99%
“…Several studies have also shown that IGF2R is expressed in many tissues, including the gut epithelium, and its expression is known to be altered in response to stressful environments such as after SBR and during the inhibition of intestinal mucosal growth (1, 2). Interestingly, the levels of mucosal miR-195 and CUGBP1 decrease in the small intestine after SBR, along with stimulation of mucosal regeneration, but their levels increase dramatically after food starvation or polyamine depletion, which is associated with an inhibition of intestinal mucosal growth (18,25,44). Moreover, IGF2R also regulates cellular processes and functions by (i) activating IGF2 signaling (42,45); (ii) promoting the cellular uptake and degradation of peptides such as proliferin, leukemia inhibitory factor, and transforming growth factor beta (TGF-␤) (4, 6); and (iii) regulating extracellular signal-regulated kinase 1/extracellular signal-regulated kinase 2 (ERK1/2) activity (32).…”
Section: Discussionmentioning
confidence: 99%
“…Biotin-labeled miRNA-195 was custom-made by Dharmacon (Lafayette, CO). The IEC-6 cell line (normal rat intestinal crypt cells) was purchased from the American Type Culture Collection (ATCC) at passage 13 and was maintained under standard culture conditions as described previously (44,46). Plasmid construction.…”
Section: Methodsmentioning
confidence: 99%